Novel Compound Heterozygous Variants in CCDC40 Associated with Primary Ciliary Dyskinesia and Multiple Morphological Abnormalities of the Sperm Flagella - Xu Y; Yang B; Lei C; Yang D; Ding S; Lu C; Wang L; Guo T; Wang R; Luo H (Dove Medical Press, 2022)
Yingjie Xu,1– 3,* Binyi Yang,1– 3,* Cheng Lei,1– 3 Danhui Yang,1– 3 Shuizi Ding,1– 3 Chenyang Lu,1– 3 Lin Wang,1– 3 Ting Guo,1– 3 Rongchun Wang,1– 3 Hong Luo1– 3 1Department of Pulmonary and Critical Care Medicine, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China; 2Research Unit of Respiratory Disease, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China; 3Hunan Diagnosis and Treatment Center of Respiratory Disease, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rongchun Wang; Hong Luo, The Second Xiangya Hospital, Central South University, 139 Renmin Middle Road, Furong District, Changsha, Hunan, 410011, People’s Republic of China, Email 198202060@csu.edu.cn; luohonghuxi@csu.edu.cnAbstract: Primary ciliary dyskinesia (PCD) is a rare genetic disease caused by mutations of genes coding motile-cilia-related proteins. CCDC40 variants can cause PCD via disrupting the assembling of inner dynein and dynein regulating complex in cilia and flagella, but none has been reported associated with multiple morphological abnormalities of the sperm flagella (MMAF). We identified and validated the disease-causing variants in our patient via whole-exome and Sanger sequencing. We used high-speed video microscopy analysis (HSVA) and immunofluorescence to analyze the functional and structural deficiency of respiratory cilia. Papanicolaou staining and scanning electron microscope was applied to analyze the morphological sperm defects resulted from the PCD associated variants. We identified novel compound variants (c.901C>T, p.(Arg301*); c.2065_2068dup, p.(Ala690Glyfs*67)) in CCDC40 in a male patient with male infertility. HSVA revealed the rigid and stiff ciliary beating pattern. Immunofluorescence indicated loss of inner dynein arm protein DNAH2 both in cilia and the sperms of the patient. Diagnosis of MMAF was confirmed through sperm Papanicolaou staining and scanning electron microscope. We first describe a patient with a combination of PCD and MMAF associated with novel compound heterozygous variants in CCDC40. Our results present initial evidence that CCDC40 associated with MMAF, which expands the genetic spectrum of PCD and MMAF and provides precise clinical genetic counseling to this family.Keywords: PCD, MMAF, CCDC40, male infertility